Isolation and characterization of pediocin L50, a new bacteriocin from Pediococcus acidilactici with a broad inhibitory spectrum. - Cintas, L M (1995)
Lactic acid bacteria were isolated from Spanish dry-fermented sausages and screened for bacteriocin production. About 10% of the isolates produced antimicrobial substances when grown on solid media, but only 2% produced detectable activity in liquid media. Strain L50, identified as Pediococcus acidilactici, showed the strongest inhibitory activity and was active against members of all of the gram-positive genera tested. The strain produced a heat-stable bacteriocin when grown at 8 to 32 degrees C but not at 45 degrees C. The bacteriocin was purified to homogeneity. Its mass was determined to be 5,250.11 +/- 0.30 by electrospray mass spectrometry. The N terminus of the bacteriocin was blocked for sequencing by Edman degradation, but a partial sequence of 42 amino acids was obtained after cleavage of the peptide by cyanogen bromide. The sequence showed no similarity to those of other bacteriocins. Pediocin L50 appears to contain modified amino acids but not lanthionine or methyl-lanthionine.